1989
DOI: 10.1016/s0022-5347(17)40595-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of the Vesicourethral Anastomosis Directing Early Decatheterization Following Nerve-Sparing Radical Retropubic Prostatectomy

Abstract: Early decatheterization directed by postoperative gravity cystography in 55 consecutive radical prostatectomy patients is described. The catheter-free status was 22 per cent by postoperative day 8, 62 per cent by postoperative day 11 and 80 per cent by postoperative day 14. Cystograms performed beginning on postoperative day 7 identified 3 groups of patients and dictated their management: 1) no extravasation resulting in immediate catheter removal (36 patients), 2) moderate extravasation requiring repeat cysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 4 publications
4
44
0
6
Order By: Relevance
“…Later appearance of the stricture implies scar formation at the stricture site and dilatation has a lower success rate. An incidence of 9% acute urinary retention after decatheterization has been reported [7]. We observed this in 4 of 340 cases.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Later appearance of the stricture implies scar formation at the stricture site and dilatation has a lower success rate. An incidence of 9% acute urinary retention after decatheterization has been reported [7]. We observed this in 4 of 340 cases.…”
Section: Discussionmentioning
confidence: 53%
“…Stricture of the vesicourethral anastomosis is a well-known complication after radical prostatectomy with most cases becoming symptomatic within the first year after surgery. The mean interval between surgery and stricture formation was discovered to be 3.8 months [7]. Other authors observed 66% of the appearance of anastomotic strictures within 6 months after radical prostatectomy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Despite agreement on surgical technique, there is no general consensus regarding the time of catheter removal [11,12,16]. Data of prospective, randomised clinical trials to clarify this issue are not available.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in patients undergoing abdominal, gynecological or vascular surgery, postoperative discomfort was significantly higher in patients with urethral versus suprapubic catheterization. [5][6][7] Although many studies have recently shown that cystography can direct early catheter removal with no increase in morbidity, 8,9 and there has been a movement towards shortened catheterization, 10,11 the optimal timing for catheter removal is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%